Feasibility and safety of non-invasive ultrasound therapy (NIUT) on an porcine aortic valve. (19th October 2020) - Messas, Emmanuel; Rémond, Mathieu C; Goudot, Guillaume; Zarka, Samuel; Penot, Robin; Mateo, Philippe; Kwiecinski, Wojciech; Escudero, Daniel Suarez; Bel, Alain; Ialy-Radio, Nathalie; Bertrand, Benjamin; Bruneval, Patrick; et al.
Abstract: Calcific aortic stenosis (CAS) is associated with advanced age and comorbidities, therefore a non-invasive therapy for it would be beneficial. We previously demonstrated that ultrasound therapy improved calcified bioprosthetic valve function in an open chest model. For translational applications, we tested non-invasive ultrasound therapy (NIUT) transthoracically on swine aortic valves and investigated the need for antithrombotic treatment as a follow-up. Primary objective: feasibility and safety of NIUT. Secondary objectives: occurrence, severity and evolution of side effects during therapy and at 1 month follow-up. The device (Valvosoft, Cardiawave) consisted of an electronically steered multi-element transducer and a 2D echocardiographic probe. Three groups of swine received treatment on aortic valves: NIUT (group 1; n = 10); NIUT and 1 month antithrombotic treatment (group 2; n = 5); sham group (group 3; n = 4). Feasibility was successfully reached in all treated swine ( n = 15) and no life-threatening arrhythmia were detected. Non-sustained ventricular tachycardia occurred during the procedure in seven swine. Decrease or interruption of NIUT ended arrhythmia. Histopathology revealed no valve or surrounding tissue damage and echocardiography revealed no valvular dysfunction. Only one animal had side effects [right ventricle (RV) dilatation], but the RV normalized after therapy cessation with no sequelae at follow-up. No disturbance in biological markers nor valve thrombosis were observed at follow-up. Antithrombotic treatment did not demonstrate any advantage. Survival at 30 d was 100%. We demonstrated, in vivo, the feasibility and safety of transthoracic NIUT on aortic valves in a swine model without serious adverse events. We expect this first-time transthoracic delivery of NIUT to pave the way towards a new non-invasive approach to valve softening in human CAS to restore valve function.